MOLECULAR IDENTIFICATION OF CYSTEINE AND TRYPSIN PROTEASE, EFFECT OF DIFFERENT HOSTS ON PROTEASE EXPRESSION, AND RNAI MEDIATED SILENCING OF CYSTEINE PROTEASE GENE IN THE SUNN PEST. Issue 4 (26th November 2015) - Amiri, Azam; Bandani, Ali Reza; Alizadeh, Houshang
Abstract : Sunn pest, Eurygaster integriceps, is a serious pest of cereals in the wide area of the globe from Near and Middle East to East and South Europe and North Africa. This study described for the first time, identification of E. integriceps trypsin serine protease and cathepsin‐L cysteine, transcripts involved in digestion, which might serve as targets for pest control management. A total of 478 and 500 base pair long putative trypsin and cysteine gene sequences were characterized and named Tryp and Cys, respectively. In addition, the tissue‐specific relative gene expression levels of these genes as well as gluten hydrolase (Gl) were determined under different host kernels feeding conditions. Result showed that mRNA expression of Cys, Tryp, and Gl was significantly affected after feeding on various host plant species. Transcript levels of these genes were most abundant in the wheat‐fed E. integriceps larvae compared to other hosts. The Cys transcript was detected exclusively in the gut, whereas the Gl and Tryp transcripts were detectable in both salivary glands and gut. Also possibility of Sunn pest gene silencing was studied by topical application of cysteine double‐stranded RNA (dsRNA). The results indicated that topically applied dsRNA on fifth nymphal stage can penetrate the cuticle of the insect and induce RNA interference. The Cys gene mRNA transcript in the gut was reduced to 83.8% 2 days posttreatment. Also, it was found that dsRNA of Cys gene affected fifth nymphal stage development suggesting the involvement of this protease in the insect growth, development, and molting.